2011
DOI: 10.2105/ajph.2009.176743
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Assessment of Community-Based Breast Health Navigation Services for Southeast Asian Women in Southern California: Recommendations for Developing a Navigator Training Curriculum

Abstract: CBHNs serve a crucial role in building trust and making screening practices culturally meaningful, accessible, usable, and acceptable. Future research should focus on developing training curricula, policies, resources, and funding to better maximize the expertise and services that CBHNs provide and to expand our findings to other underserved communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 23 publications
0
34
1
Order By: Relevance
“…53 Knowledge of specific and general medical information has been linked to health behaviors such as screening. 50,51,[54][55][56][57] Findings from the present study suggest that Chinese Americans with higher collectivism views were more willing to participate in biospecimen research compared with those with less collectivism views, although this did not remain significant in multivariate analyses. Collectivists value actions with benefits to society and social life [23][24][25][26][27][28] and so support medical research by being willing to donate blood.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…53 Knowledge of specific and general medical information has been linked to health behaviors such as screening. 50,51,[54][55][56][57] Findings from the present study suggest that Chinese Americans with higher collectivism views were more willing to participate in biospecimen research compared with those with less collectivism views, although this did not remain significant in multivariate analyses. Collectivists value actions with benefits to society and social life [23][24][25][26][27][28] and so support medical research by being willing to donate blood.…”
Section: Discussioncontrasting
confidence: 64%
“…Many other studies indicate that trust in health care is linked to better health screening, adherence to medication, and satisfaction with health care. 7,8,[45][46][47][48][49][50][51] CBPR best practices suggest that including scientists and clinicians from respected health institutions in community partnerships builds community trust and may help to increase community involvement in biobanking. 52 Knowledge about biospecimen research plays an important role in Chinese American willingness to participate in biospecimen research as indicated by our bivariate results.…”
Section: Discussionmentioning
confidence: 99%
“…While PN and similar models, such as community health workers and promotoras, are intended to provide emotional support and information,[4, 8, 13, 25–28] there is relatively little known about patients’ perceptions of social support from navigators or community health workers. [2931] Wagner et al reported that patients randomized to nurse navigators reported being more involved in their care, more informed about how cancer affects their life and better prepared for the future.…”
Section: Discussionmentioning
confidence: 99%
“…As other studies have described, training programs often offer inadequate support in dealing with clients' interpersonal issues. 21,22 Our peer coaches stated that these skills were as important, if not more so, than the content-oriented skills they were taught. Training programs should also provide a realistic picture of the coaching role.…”
Section: Discussionmentioning
confidence: 94%